Comparison of Cerebral Blood Flow Patterns in Patients with Phantom Bite Syndrome with Their Corresponding Clinical Features - Umezaki Y (Dove Medical Press, 2020)
Yojiro Umezaki,1 Motoko Watanabe,2 Yukiko Shinohara,2 Shiori Sugawara,2 Kaoru Kawasaki,2 Trang TH Tu,2 Takeshi Watanabe,2 Takayuki Suga,2 Anna Miura,2 Miho Takenoshita,2 Yusuke Sato,3 Ichiro Minami,4 Jun Oyama,5 Akira Toriihara,5 Tatsuya Yoshikawa,2 Toru Naito,1 Haruhiko Motomura,2 Akira Toyofuku2 1Section of Geriatric Dentistry, Department of General Dentistry, Fukuoka Dental College, Fukuoka 814-0193, Japan; 2Department of Psychosomatic Dentistry, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo 113-8548, Japan; 3Department of Gerontology and Gerodontology, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo 113-8548, Japan; 4Department of Removable Partial Prosthodontics, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo 113-8548, Japan; 5Department of Diagnostic Radiology and Nuclear Medicine, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, Tokyo 113-8548, JapanCorrespondence: Akira ToyofukuDepartment of Psychosomatic Dentistry, Graduate School of Medical and Dental Sciences, Tokyo Medical and Dental University, 1-5-45 Yushima, Bunkyo-Ku, Tokyo 113-8548, JapanTel/Fax +81- 3-5803-5909Email toyoompm@tmd.ac.jpBackground: Phantom bite syndrome (PBS) is characterized by an uncomfortable sensation during occlusion without any evident abnormality. A recent case–control study with single-photon emission computed tomography (SPECT) using 99mTc-ethyl cysteinate dimer could not find the specific features of regional cerebral blood flow (rCBF), which might be due to the heterogeneity of PBS. We analyzed the brain images of PBS corresponding to the clinical features by studying PBS subgroups.Methods: This study contributes to elucidating the pathophysiology of PBS by evaluating regional brain perfusion on SPECT and its clinical features. We performed SPECT using 99mTc-ethyl cysteinate dimer in 44 patients with PBS. The SPECT images were analyzed qualitatively and quantitatively.Results: Asymmetrical rCBF patterns were detected, corresponding to symptom laterality. Patients with PBS with right-side symptoms showed right-side-predominant rCBF asymmetry in the parietal region and left-side-predominant rCBF asymmetry in the thalamus, and vice versa. Moreover, the analysis of the association between rCBF and patient behaviors revealed that patients who blamed their dentists for their symptoms tended to have a symmetrical rCBF pattern.Conclusion: Patients with PBS showed blood flow imbalance in the thalamus and parietal region corresponding to symptom laterality. There are two types of symmetrical and asymmetrical rCBF patterns in the pathophysiology of PBS despite similar clinical manifestations.Keywords: phantom bite syndrome, cerebral blood flow, single-photon emission computed tomography